The key role of miRNA in syndromic and sporadic forms of ascending aortic aneurysms as biomarkers and targets of novel therapeutic strategies - Terriaca, Sonia; Monastero, Roberto; Orlandi, Augusto; Balistreri, Carmela Rita (Frontiers in Genetics, 2024)
Increasing evidence shows that epigenetics also plays a key role in regulating the pathogenetic mechanism of all types of aortic aneurysms. It is well-known that epigenetic factors modulate gene expression. This mechanism appears to be of interest especially knowing the relevance of genetic susceptibility and genetic factors in the complex pathophysiology of aortic aneurysms, and of sporadic forms; in fact, the latter are the result of a close interaction between genetic and modifiable lifestyle factors (i.e. nutrition, smoking, infections, use of drugs, alcohol, sedentary lifestyle, etc.). Epigenetic factors include DNA methylation, post-translational histone modifications, and non-coding RNA.Here, our attention is focused on the role of miRNA in syndromic and sporadic forms of thoracic aortic aneurysms. They could be both biomarkers and targets of novel therapeutic strategies.